The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Modeling V2G spot market trading: The impact of charging tariffs on economic viability - Tim Signer; Nora Baumgartner; Manuel Ruppert; Thorben Sandmeier; Wolf Fichtner (Energy Policy, 2024)

Using in-situ strain measurements to evaluate the accuracy of stress estimation procedures from fracture injection/shut-in tests - Yves Guglielmi; Mark McClure; Jeffrey Burghardt; Joseph P. Morris; Thomas Doe; Pengcheng Fu; Hunter Knox; Vince Vermeul; Tim Kneafsey; J. Ajo-Franklin; T. Baumgartner; K. Beckers; et al. (International Journal of Rock Mechanics and Mining Sciences, 2023)

Evaluation of a new practical low-cost method for prioritising the remediation of fish passage barriers in resource-deficient settings - Tim Marsden; Lee J. Baumgartner; Deanna Duffy; Ana Horta; Nathan Ning (Ecological Engineering, 2023)

Using fish swimming ability to refine criteria for fishway construction in Myanmar - John Conallin; Nyi Nyi Tun; Aye Myint Swe; Lee J. Baumgartner; Zau Lunn; Martin Mallen-Cooper; Tim Marsden; Nathan Ning; Wayne Robinson; Lalantha Senevirathna; Peter Thew (Fisheries Research, 2023)

Multifarious anchovy and sardine regimes in the Humboldt Current System during the last 150 years - Renato Salvatteci; David Field; Dimitri Gutiérrez; Tim Baumgartner; Vicente Ferreira; Luc Ortlieb; Abdel Sifeddine; Daniel Grados; Arnaud Bertrand (Global Change Biology, 2018)
The Humboldt Current System ( HCS ) has the highest production of forage fish in the world, although it is highly variable and the future of the primary component, anchovy, is uncertain in the context of global warming. Paradigms based on late 20th century observations suggest that large‐scale forcing controls decadal‐scale fluctuations of anchovy and sardine across different boundary currents of the Pacific. We develop records of anchovy and sardine fluctuations since 1860 AD using fish scales from multiple sites containing laminated sediments and compare them with Pacific basin‐scale and regional indices of ocean climate variability. Our records reveal two main anchovy and sardine phases with a timescale that is not consistent with previously proposed periodicities. Rather, the regime shifts in the HCS are related to 3D habitat changes driven by changes in upwelling intensity from both regional and large‐scale forcing. Moreover, we show that a long‐term increase in coastal upwelling translates via a bottom‐up mechanism to top predators suggesting that the warming climate, at least up to the start of the 21st century, was favorable for fishery productivity in the HCS .

Short-Term Cuprizone Feeding Verifies N-Acetylaspartate Quantification as a Marker of Neurodegeneration - Barbara Maria Krauspe; Wolfgang Dreher; Cordian Beyer; Werner Baumgartner; Bernd Denecke; Katharina Janssen; Claus-Dieter Langhans; Tim Clarner; Markus Kipp (Journal of Molecular Neuroscience, 2015)

ADRB2 G–G haplotype associated with breast cancer risk among Hispanic and non-Hispanic white women: interaction with type 2 diabetes and obesity - Avonne Connor; Richard N. Baumgartner; Richard A. Kerber; Elizabeth O’Brien; Shesh N. Rai; Roger K. Wolff; Martha L. Slattery; Anna R. Giuliano; Betsy C. Risendal; Tim E. Byers; Kathy B. Baumgartner (Cancer Causes & Control, 2012)

Cuprizone Treatment Induces Distinct Demyelination, Astrocytosis, and Microglia Cell Invasion or Proliferation in the Mouse Cerebellum - Angela Groebe; Tim Clarner; Werner Baumgartner; Jon Dang; Cordian Beyer; Markus Kipp (The Cerebellum, 2009)

Family history and age at onset of breast cancer in Hispanic and non-Hispanic white women - Betsy Risendal; Lisa M. Hines; Carol Sweeney; Martha L. Slattery; Anna R. Giuliano; Kathy B. Baumgartner; Karen Curtin; Tim E. Byers (Cancer Causes & Control, 2008)

Reproductive history in relation to breast cancer risk among Hispanic and non-Hispanic white women - Carol Sweeney; Kathy B. Baumgartner; Tim Byers; Anna R. Giuliano; Jennifer S. Herrick; Maureen A. Murtaugh; Martha L. Slattery (Cancer Causes & Control, 2008)

Genetic, Anthropometric, and Lifestyle Factors Associated with IGF-1 and IGFBP-3 Levels in Hispanic and Non-Hispanic White Women - M. L. Slattery; K. B. Baumgartner; Tim Byers; Anna Guiliano; Carol Sweeney; Jennifer Herrick; Karen Curtin; Maureen Murtaugh; Roger Wolff (Cancer Causes & Control, 2005)